Titanium Dioxide (IntechOpen, 2023)
Titanium dioxide is currently being used in many industrial products. It provides unique photocatalytic properties for water splitting and purification, bacterial inactivation, and organics degradation. It has also been widely used as the photoanode for dye-sensitized solar cells and coatings for self-cleaning surfaces, biomedical implants, and nanomedicine. This book covers various aspects of titanium dioxide nanomaterials including their unique one-dimensional, two-dimensional, mesoporous, and hierarchical nanostructures and their synthetic methods such as sol-gel, hydrothermal, anodic oxidation, and electrophoretic deposition, as well as its key applications in environmental and energy sectors. Through these 24 chapters written by experts from the international scientific community, readers will have access to a comprehensive overview of the recent research and development findings on the titanium dioxide nanomaterials.